DEVELOPMENT OF ETHNOMATEMATICS-BASED SOCIAL ARITHMETIC LKPD WITH A CONTEXTUAL APPROACH AT MAIMUN PALACE TO INCREASE LEARNING INTEREST - zulayli syahrani; Ella Andhany (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to develop Student Worksheets (LKPD) on social arithmetic material based on ethnomathematics with a contextual approach through the context of Maimun Palace to increase the learning interest of students in class VIII-1 at Cerdas Murni Junior High School. The approach used in this study is the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of validation by subject matter, media, and language experts showed that the developed LKPD was in the highly valid category with an average score of 0.84. The practicality test conducted by teachers and students obtained an average score of 4.08, which was classified as highly practical, and the results of the student response questionnaire classification were in the strong category with a percentage of 79.57%. Furthermore, the effectiveness of the LKPD was observed through the results of a student learning interest questionnaire, which showed an increase from an average of 59.33% to 76.97%, which is classified as effective. Thus, the ethnomathematics-based social arithmetic LKPD through a contextual approach is declared valid, practical, and effective in supporting the mathematics learning process and can increase students' conceptual understanding and learning interest. The results of this study are expected to become an alternative innovative teaching material that supports more contextual learning activities and is in line with how the brain works.